Solanum lycopersicum L. CGN15498 ... - GLIS Of The ITPGRFA (Centre for Genetic Resources, the Netherlands, 2017)
Plant Genetic Resource. Taxonomy: Solanum lycopersicum L. Common name(s): tomato Other names: Early Sub-Arctic Conserved by: Centre for Genetic Resources, the Netherlands (CGN), Netherlands (Kingdom of the) Local sample unique identifier: CGN15498 Method of creation: Acquisition Date: 1993-08-12 Other identifiers: purl,http://purl.org/cgngenis/accenumb/CGN15498, n/a,1.1492 Historical: No Biological status: Advanced or improved cultivar MLS status: Not included ...